PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS AUDIO VISUAL TENTANG PEMBUATAN KOLOID - Anjar Purba Asmara (Center for Research and Publication Universitas Islam Negeri (UIN) of Ar-Raniry, 2015)
This is a developing research of learning media which aimed to create media of audio visual for the practicum of colloid and to get quality score of the media. The creating of the media has been consulted by two experts of media and three peer reviewers. The research instrument is questionnaire that contains aspects and criteria of quality scoring. The scoring had been given by five chemistry teachers at excellent senior high school. The result of the research is a audio visual media which burnt on CD. It contains practicum about making of colloid by disperse method and condentation method. Based on the scoring from reviewer 1, the media is classified to good quality with the mean score is 138.5. The media is classified to very good quality by scoring from reviewer 2. By testing in classroom, colloid learning by using audio visual media gives more satisfy result than learning without the media.